PROSEDUR PEMBERIAN INSENTIF DAN KEMUDAHAN INVESTASI DI KOTA PALEMBANG - Suci Flambonita; Vera Novianti (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2021)
The important factors in the framework of realizing people's welfare is economic growth, which can be encouraged through the creation of a conducive investment climate that contributes to economic growth and improvement of welfare society, to support the realization of sustainable and quality economic growth, of investment climate. attractive, encouraging investment to increase the competitiveness of the national economy, as well as increasing the capacity of adequate infrastructure and other supporting factors, including the provision of incentives and ease of investment in the city of Palembang. The normative method is carried out through a literature study that examines (especially) secondary data in the form of laws and regulations, or other legal documents, as well as research results, study results, and other references. The method used normative legal research, which includes secondary legal materials and is developed with primary legal materials from theoretical instruments. In addition to collecting the type of data used in this study is secondary data, which was obtained through a library study. The procedure for providing incentives and ease of investment in Palembang based on external and internal considerations, the basic principles of establishing procedures for providing incentives and investment facilities, criteria for investment activities, as well as regional classification criteria, the provision of incentives and investment facilities is determined, which in turn establishes a rule regarding the establishment of procedures providing incentives and investment.